Solomon Islands : Second Review Under the Standby Credit Facility and Request for a Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report, 2012)
This paper is an account of the economic conditions of the Solomon Islands. The macroeconomic situation has shown a considerable expansion in recent years with the external buffers intact. Although the Islands have shown good growth, the IMF staff expects only a moderate performance in 2013 and 2014 owing to the euro area crisis. However, the state has prepared for any downside risks, and approaches the macroeconomic circumstances with a positive outlook. The Executive Board admires the efforts of the Islands.